The Emerging Role of National Academies in Surgical Training: An Inspiring Environment for Increasing the Quality of Health Care in Breast Cancer Management - GÜLLÜOĞLU, MAHMUT BAHADIR (SPRINGER, 2014)
Medical education, both graduate and postgraduate, is given at medical schools and affiliated teaching hospitals. The training at these institutions is necessary and valuable. In each field of the medical profession, the relevant science is being developed and changed constantly. Training of medical staff and auxilliary professionals must be adaptable to changes in the field. Also, the development of standards for the diagnosis and treatment of diseases is important. Independent institutions, called academies, serve an extremely useful task in the continuing further training that needs to be adjusted according to individual needs. Academies are independent and free from bureaucracies. Standardized records are uniform and comparable at these institutions. Both patients and medical staff receive training from these institutions. In this way, a high standard is provided in medicine, error rates are decreased and patient satisfaction is increased. Breast cancer, the most common tumor in women, is a serious cause of morbidity and mortality. The European Institute of Oncology (EIO) in Milan, Italy and the European Academy of Senology in Duesseldorf, Germany play important roles in establishing the standards of breast care. They provide substantial training for physicians to achieve high quality in breast cancer management. SENATURK (Senoloji Akademisi, Turkish Academy of Senology) was established in 2010 in Istanbul, Turkey. Both national and international scientists and physicians including eminent senologists are currently faculty members of this young organization. SENATURK collaborates with other institutions in Europe. Its missions include developing training programs for each level of the profession, as well as developing data recording systems and electronic learning tools for breast cancer prevention, diagnosis, treatment, rehabilitation and palliation. Briefly, SENATURK plays a significant role as the opinion leader on every aspect of health care related to conditions and diseases of the breast.
Keywords: Medical academy; Postgraduate medical education; In-training education; Senology; Breast diseases; Breast cancer; EDUCATION; ASSURANCE; DIAGNOSIS; GERMANY